(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2023)
This paper examines the various forms of alienation and identity in Joseph Diescho’s Troubled Waters. According to Hussam, (2013), Alienation and Identity Crisis form the subject of many psychological, sociological, literary and philosophical studies. Hussam (2013) goes on to say that these are major themes of human condition in the contemporary epoch. It is hoped that the paper, will help students, researchers and teachers in enhancing interest and encouraging them to explore Alienation and Identity Crisis in any genres of their interests. The paper will therefore look at the plot, Diescho’s technique and a concluding remark on the novel as a whole, major characters associated with alienation and identity crisis and an analysis on the objectives in this paper. The two main objectives in this paper are: To identify and examine how Joseph Diescho presents the concept of alienation and identity crisis in Troubled Waters and to examine the experiences of the major characters in Troubled Waters and extract lessons learnt.